Analysis of the complete mtDNA in Brazilian samples: Haplotypes differentiation and identification of new variations in Native American haplogroups - DF, Braganholi [UNESP]; JM, Freitas; NC, Andrekenas [UNESP]; BB, Januário [UNESP]; IB, Ambrosio [UNESP]; FS, Polverari [UNESP]; RMB, Cicarelli [UNESP] (Elsevier, 2019)
Initial data about the population of the Center-West Brazil region for mtDNA CR were published in 2019. From this group, 74 samples were selected from individuals who shared haplotypes. The purpose was to analyze the complete mtDNA by Massively Parallel Sequencing and to evaluate if it is possible to differentiate these haplotypes. Libraries were created for all samples and to date 22 samples were sequenced by the Illumina system. Analyzing only the CR, 8 haplotypes were identified in these 22 samples. The complete mtDNA analysis allowed the identification of 16 haplotypes, 6 of which were shared by two samples each, that is, the diversity of haplotypes in this sample increased. In addition, we identified some genetic variants not reported in the EMPOP in mtDNAs classified in haplogroups A2, B2, L2a1f and L0a2a2a.
Keywords: Brazil; Center-west region; Human identification; mtDNA